A Bibliometric Analysis of Sustainable Supply Chain Management Literature: Insights From the Web of Science Database - ÖZKAN, Ahmet Murat; BAYRAKÇIL, Ali Oğuz (Asosiasi Ahli Administrasi Indonesia, 2026)
This study presents a comprehensive bibliometric review of the open-access sustainable supply chain management (SSCM) literature, analyzing 5,866 articles indexed in the Web of Science. It aims to map the field’s intellectual structure, evolution, and emerging research trends using techniques such as performance analysis, co-citation analysis, keyword co-occurrence and thematic evolution analysis. The findings indicate a rapid expansion of SSCM research, particularly since 2010, driven by growing interest in integrating sustainability into supply chain practices. While early studies primarily emphasized environmental concerns under the green supply chain paradigm, recent research adopts a more holistic perspective that incorporates economic, environmental and social dimensions. Emerging themes include circular economy practices, digitalization and Industry 4.0, resilience and risk management and sustainable innovation. The analysis further identifies distinct developmental phases in the SSCM literature, from conceptual foundations to empirical and methodological advancement. Additionally, the results reveal a divergence between collaboration intensity and citation impact: although a core group of authors dominates publication output, highly cited work is often produced by more dispersed scholars. This suggests that scholarly influence in SSCM is largely driven by interdisciplinary and conceptually innovative contributions, offering important implications for future research and collaboration strategies.